2014
DOI: 10.1016/j.watres.2014.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Biomass retention on electrodes rather than electrical current enhances stability in anaerobic digestion

Abstract: Anaerobic digestion (AD) is a well-established technology for energy recovery from organic waste streams. Several studies noted that inserting a bioelectrochemical system (BES) inside an anaerobic digester can increase biogas output, however the mechanism behind this was not explored and primary controls were not executed. Here, we evaluated whether a BES could stabilize AD of molasses. Lab-scale digesters were operated in the presence or absence of electrodes, in open (no applied potential) and closed circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(55 citation statements)
references
References 55 publications
3
50
2
Order By: Relevance
“…Although acetoclastic/hydrogenotrophic methanogenesis cannot be ruled out, the introduction of the electrodes enhanced the methanogenic processes as a consequence of better biomass proliferation, as observed from the responses obtained from OC experiments versus CC tests. In these experiments, applying an electric charge did not cause higher methane production rates, which was in accordance with results reported by De Vrieze et al [23]. The measurement of the electric current of the closed-circuit system allows for the calculation of the methane produced by electromethanogenesis using the stoichiometry of this reaction.…”
Section: Methane Production and Current Profilessupporting
confidence: 91%
See 1 more Smart Citation
“…Although acetoclastic/hydrogenotrophic methanogenesis cannot be ruled out, the introduction of the electrodes enhanced the methanogenic processes as a consequence of better biomass proliferation, as observed from the responses obtained from OC experiments versus CC tests. In these experiments, applying an electric charge did not cause higher methane production rates, which was in accordance with results reported by De Vrieze et al [23]. The measurement of the electric current of the closed-circuit system allows for the calculation of the methane produced by electromethanogenesis using the stoichiometry of this reaction.…”
Section: Methane Production and Current Profilessupporting
confidence: 91%
“…In addition, a combined AD and BES (AD-BES) reactor could represent a useful way to prevent inhibition of the AD process in pre-installed digesters, optimizing the efficiency and treatment capacity of pre-existing infrastructure. In fact, this combined approach has been evaluated for the treatment of different substrates, such as fecal wastewater [20], waste activated sludge [21,22], molasses [23], domestic wastewater [24], and toxic contaminants [25]. However, these studies were performed at non-inhibitory organic loads and offered no information on how the combined AD-BES reactor behaves when VFAs accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study performed concluded that such anode biofilms increase the retention of slowly growing microorganisms (e.g., acetoclastic methanogens) in the EAD and thus enhance the rate of anaerobic digestion (De Vrieze et al, 2014). However, in our study, such thick biofilms were not observed on the graphite brushes in the control digester, indicating that solid retention near the graphite brush did not play an important role in enhancing the rate of anaerobic digestion in this study.…”
Section: Potential Retention Of Slowly Growing Microorganisms Near Bicontrasting
confidence: 87%
“…Previous studies that have reported stimulation in methane production when carbon cloth was introduced into digesters have attributed this response to the cloth retaining methanogens (48)(49)(50). However, the possibility that these conductive materials might promote DIET should also be considered.…”
Section: Resultsmentioning
confidence: 99%